Effect of inclusion of Rice Dried Distillers Grain Soluble (RDDGS) at varying levels with or without enzyme supplementation on growth performance of Japanese quails: RDDGS in Japanese quails diets performance - Y.V.S. RAJESH; D. NARENDRANATH; K. NAGA RAJA KUMARI; P. KAVITHA (Indian Journal of Poultry Science, 2025)
The study was conducted to assess the effect of dietary incorporation of rice distiller dried grain solubles (RDDGS) with or without enzyme supplementation on growth performance of Japanese quails. Day-old Japanese quails (N=180) were distributed randomly into six dietary groups each with three replicates of 10 birds. Six experimental diets were formulated by inclusion of RDDGS at 0% (Basal diet, T1), 0% (Basal diet with enzyme, T2), 20% (T3), 20% (with enzyme, T4), 25% (T5) and 25% (with enzyme, T6) levels by marginal adjustment of other feed ingredients and fed for a period of five weeks. Results revealed that inclusion of RDDGS up to 20% with enzyme had significant positive influence on body weight and body weight gain (p<0.01), lower the feed intake (p<0.01) and better FCR (p<0.01). The nutrient digestibility wasn’t differed significantly. The feed cost per kg live weight gain was significantly lowest in T4 group (20% with enzyme). Basing on the findings, it can be concluded that RDDGS can be incorporated up to 20 per cent level with enzyme supplementation in diets of quails for economic production.